Pengaruh Model Pembelajaran Bermain Peran Terhadap Hasil Belajar Pembelajaran IPS Siswa Kelas V SD - Agus Irawan; Sri Dadi (JURIDIKDAS, 2023)
This study aims to determine the effect of models role playing on the results of social studies learning in fifth grade students of Elementary School Group XIII Bengkulu City. This research is quantitative research. The research used was a quasy experiment with a matching only pretest-posttest control group design study design. The population in this study was SD Cluster XIII Bengkulu City. The sampling technique uses cluster random sampling. The sample in this study was elementary school with B accreditation and KTSP curriculum. Class V at SDN 77 with students as many as 32 students as the experimental class and class V at SDN 83 with students as many as 30 students as the control class. The instrument used is a multiple choice test sheet.. Data analysis techniques used descriptive statistical analysis, prerequisite test analysis, and hypothesis test analysis. From the results of the study it is known that the results of the t-test obtained by tcount 1.850> t table 1.673. So, the conclusion is that there is an influence of discovery learning through media images on the results of social studies learning in fifth grade students of Elementary School Group XIII Bengkulu City.